Morphoroxydine hydrochloride tablet and preparation method thereof
By strictly controlling the particle size of morpholine guanidine hydrochloride and the model and composition of auxiliary materials, and optimizing the preparation method, the prepared morpholine guanidine hydrochloride tablets have a high and stable dissolution, which solves the problem of unstable dissolution of existing morpholine guanidine hydrochloride tablets and improves the patient's medication experience.
Patent Information
- Application Number
- CN202510020121.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2045-01-07
AI Technical Summary
The dissolution of morpholin guanidine hydrochloride tablets is unstable, resulting in quality differences between different manufacturers and the same batch. Especially for patients with viral infections and swallowing disorders, the bitter taste of the drug will affect the patient's medication experience.
By strictly controlling the particle size of morpholine guanidine hydrochloride and the model, composition, particle size of auxiliary materials, etc., and optimizing the preparation method, the obtained morpholine guanidine hydrochloride tablets have high dissolution and stable dissolution. The specific method includes the use of morpholinguanidine hydrochloride with a particle size of 15-20 μm and D50 is 8-12 μm. The core of the sheet is composed of morpholinguanidine hydrochloride, microcrystalline cellulose, lactose, croscarmellose sodium, povidone K25 and magnesium stearate. The coating is composed of ethyl cellulose, maltose, talc, titanium dioxide and povidone K25, and coated by a spray coating machine.
The prepared morpholin hydrochloride guanidine tablets have high dissolution and stable dissolution, with no less than 85% within 30 minutes, and the dissolution between the same batches is stable, improving the patient's medication experience.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of pharmaceutical preparations and relates to a morpholinoguanidine hydrochloride tablet and a preparation method thereof. Background Art
[0002] Moroxydine Hydrochloride, also known as morpholine imidazole, morpholine biguanide, virus spirit, ABOB, chemical name NN-(2-guanidino-ethylimino)-morpholine hydrochloride, the structural formula is shown below, it is an antiviral drug. It is easily soluble in water and tastes slightly bitter; it can inhibit viral DNA and RNA polymerase, thereby inhibiting viral reproduction. In vitro, 1% concentration has a significant inhibitory effect on DNA viruses (adenovirus, herpes virus) and RNA viruses (echovirus), and has an inhibitory effect on all stages of the viral proliferation cycle.
[0003]
[0004] Domestic preparations of guanidine hydrochloride mainly include guanidine hydrochloride tablets, guanidine hydrochloride injection, and guanidine hydrochloride eye drops. Among them, guanidine hydrochloride tablets have the most manufacturers, more than 200. The Drug Instrument Inspection Institute of the Joint Logistics Department of the Beijing Military Region has conducted sampling tests on this drug. The results show that the dissolution rate meets the requirements. There are obvious differences in the quality of guanidine hydrochloride tablets produced by different manufacturers, and even the same batch of the same manufacturer has obvious differences, which is mainly reflected in the dissolution behavior.
[0005] Morphoguanidine hydrochloride tablets are oral tablets that are simple and convenient to take, but they taste bitter. For patients with swallowing disorders caused by viral infections, the drug may cause throat blockage and may dissolve. The bitter taste of the drug will affect the patient's medication experience.
[0006] Therefore, it is necessary to further study the formulation and preparation method of morpholino hydrochloride tablets to improve the dissolution behavior of morpholino hydrochloride tablets and the patient's medication experience. Summary of the invention
[0007] The inventors of the present invention unexpectedly found during their research that by strictly controlling the particle size of morpholino hydrochloride and the model, composition, particle size, etc. of the auxiliary materials and optimizing the preparation method, the prepared morpholino hydrochloride tablets have high and stable solubility and stable quality after accelerated storage for 6 months.
[0008] First, the present invention provides a morpholino hydrochloride tablet, comprising a tablet core and a coating, wherein the tablet core is made of the following raw materials in percentage by weight: 32%-45% morpholino hydrochloride, 20%-25% microcrystalline cellulose, 25%-30% lactose, 3%-8% cross-linked carboxymethyl cellulose sodium, and povidone K. 25 3%-5%, magnesium stearate 1.2%-2%; the particle size of the morpholino hydrochloride is D90 15-20μm, D 50 The microcrystalline cellulose is preferably microcrystalline cellulose KG802.
[0009] In some embodiments of the present invention, the tablet core is made of the following raw materials in percentage by weight: 35%-40% morpholino hydrochloride, 21%-24% microcrystalline cellulose, 25%-30% lactose, 3%-8% cross-linked carboxymethyl cellulose sodium, and povidone K. 25 3%-5%, magnesium stearate 1.2%-2%.
[0010] In some embodiments of the present invention, the tablet core is made of the following raw materials in weight percentage: 36%-39% of morpholino hydrochloride, 20%-25% of microcrystalline cellulose, 25%-30% of lactose, 3%-8% of cross-linked carboxymethyl cellulose sodium, and 1%-2% of polyvinylpyrrolidone. 25 3%-5%, magnesium stearate 1.2%-2%.
[0011] In some embodiments of the present invention, the tablet core is made of the following raw materials in weight percentage: 36%-39% of morpholino hydrochloride, 21%-24% of microcrystalline cellulose, 25%-30% of lactose, 3%-8% of cross-linked carboxymethyl cellulose sodium, and 1%-2% of polyvinylpyrrolidone. 25 3%-5%, magnesium stearate 1.2%-2%.
[0012] The microcrystalline cellulose is preferably microcrystalline cellulose KG802.
[0013] The particle size D of the morpholino hydrochloride 90 15-20μm, D 50 8-12μm.
[0014] Furthermore, the coating is made of the following raw materials in weight percentage: 35%-50% ethyl cellulose, 35%-50% maltose, 1.2%-2.0% talcum powder, 2%-3% titanium dioxide, and povidone K. 25 5%-10%.
[0015] In some embodiments of the present invention, the coating is made of the following raw materials in weight percentage: ethyl cellulose 32%-37%, maltose 32%-37%, talc 1.2%-2.0%, titanium dioxide 2%-3%, povidone K 25 5%-10% Furthermore, the ratio of coating weight to tablet core weight is 8-12:1, preferably 10:1.
[0016] Furthermore, the morpholino hydrochloride tablets contain 0.1 g to 0.5 g of morpholino hydrochloride, preferably 0.1 g.
[0017] Another object of the present invention is to provide a method for preparing the morpholineguanidine tablets.
[0018] (1) Pretreatment of auxiliary materials; ① Mix microcrystalline cellulose and lactose, grind them into a powder with an average particle size of 30-40 μm, and obtain a microcrystalline cellulose lactose mixture for later use.
[0019] ②Polyvidone K25 is dissolved in water to prepare a solution with a concentration of 5wt%-10wt% as an adhesive solution for later use.
[0020] ③ Ethyl cellulose, maltose, talcum powder, titanium dioxide, povidone K 25 Add ethanol in an amount of 20-25 times the weight of the coating, stir, and homogenize to obtain a coating solution for use.
[0021] (2) Premixing and wet granulation: Adding guanidine hydrochloride, microcrystalline cellulose lactose mixture and cross-linked carboxymethyl cellulose sodium into a wet mixing granulator for stirring and premixing, and then adding a binder solution under stirring conditions, wet granulating; controlling the injection speed of the binder solution, spraying the binder solution evenly, making the duration of the binder solution injection process 140-180 seconds, and the granulation time after the injection is completed is 120-180 seconds; (3) Drying and granulation: Dry at 50-55℃, and the drying loss is not higher than 1.2%; the dried granules are added to a granulator, and the sieve aperture of the granulator is 2.0mm; (4) Tableting: Add magnesium stearate to the granules and press into tablets to obtain tablet cores.
[0022] (5) Coating: The coating is performed by a spray coating machine until the coating weight gain reaches 5 wt%-7 wt%. The coating is then cured and dried at room temperature to obtain morpholinoguanidine hydrochloride tablets.
[0023] In step (3), the temperature is preferably 52-54°C, and more preferably dried under reduced pressure and vacuum.
[0024] In step (2), the particle size D of guanidine hydrochloride is 90 15-20μm, D 50 8-12μm.
[0025] Furthermore, in the step (3), the particles are granulated, and the particle size distribution of the particles after granulation is:
[0026] Furthermore, in step (5), each tablet contains 0.1 g of morpholinoguanidine hydrochloride and weighs 0.25-0.30 g.
[0027] The invention optimizes the preparation method by strictly controlling the particle size of morpholino hydrochloride and the model, composition, particle size and the like of auxiliary materials, so that the prepared morpholino hydrochloride tablets have high and stable dissolution and stable quality after accelerated storage for 6 months. DETAILED DESCRIPTION
[0028] The present invention discloses a method for preparing morpholino hydrochloride tablets. Those skilled in the art can refer to the content of the present invention, combine the relevant principles of pharmaceutical preparations, and appropriately improve the process parameters to achieve the method. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the scope of the present invention. The application of the present invention has been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to achieve and apply the technology of the present invention.
[0029] In order to better understand the present invention but not to limit the scope of the present invention, all the numbers expressing the amount, percentage, and other numerical values used in this application should be understood to be modified by the word "about" in all cases. Each numerical parameter should at least be considered to be obtained based on the reported significant figures and by conventional rounding methods.
[0030] The present invention is further described below by way of examples, but the examples do not limit the present invention in any way.
[0031] The particle size of morpholinoguanidine hydrochloride used in the embodiments of the present invention is shown in the following table:
[0032] Determination of dissolution curve Dissolution medium: water; 1000ml; rotation speed: 50 rpm Sampling time: 3min, 6min, 10min, 15min, 20min, 30min Example 1-3: Morphoguanidine hydrochloride tablets 1. Prescription composition:
[0033] The materials were added according to the prescription quantity of 10,000 tablets to prepare morpholinoguanidine hydrochloride tablets. The same applies below.
[0034] 2. Preparation method: (1) Pretreatment of auxiliary materials; ① Mix and grind microcrystalline cellulose and lactose to obtain a microcrystalline cellulose lactose mixture with average particle sizes of 32.1 μm, 33.6 μm and 35.7 μm, respectively, for later use.
[0035] ②Polyvidone K25 is dissolved in water to prepare a solution with a concentration of 7 wt % as an adhesive solution for later use.
[0036] ③ Ethyl cellulose, maltose, talcum powder, titanium dioxide, povidone K 25 Add ethanol in an amount of 22 times the weight of the coating, stir, and homogenize to obtain a coating solution for use.
[0037] (2) Premixing and wet granulation: Adding guanidine hydrochloride, microcrystalline cellulose lactose mixture and cross-linked carboxymethyl cellulose sodium into a wet mixing granulator for stirring and premixing, and then adding a binder solution under stirring conditions for wet granulation; controlling the injection speed of the binder solution and spraying the binder solution evenly, so that the duration of the process of spraying the binder solution is 160 seconds, and the granulation time after the spraying is completed is 150 seconds; (3) Drying and granulation: Dry at 52-54℃, and the drying loss is not higher than 1.2%; the dried granules are added to a granulator, and the sieve aperture of the granulator is 2.0mm;
[0038] (4) Tableting: Add magnesium stearate to the granules and press into tablets to obtain tablet cores.
[0039] (5) Coating: Coating is performed using a spray coating machine until the coating weight gain reaches 6 wt %. The coating is then cured and dried at room temperature for 48 hours to obtain morpholino hydrochloride tablets.
[0040] 3. Test results: The dissolution curve of the prepared morpholino hydrochloride tablets in water was measured, and the results are shown in the following table.
[0041]
[0042] Example 4-6: Morphoguanidine hydrochloride tablets 1. Prescription composition:
[0043] 2. Preparation method: (1) Pretreatment of auxiliary materials; ① Mix microcrystalline cellulose and lactose, grind them into average particle sizes of 31.1 μm, 36.4 μm and 38.8 μm respectively, and obtain a microcrystalline cellulose lactose mixture for later use.
[0044] ②Polyvidone K25 is dissolved in water to prepare a solution with a concentration of 8 wt %, which is used as an adhesive solution for later use.
[0045] ③ Ethyl cellulose, maltose, talcum powder, titanium dioxide, povidone K 25Add ethanol in an amount of 22 times the weight of the coating, stir, and homogenize to obtain a coating solution for use.
[0046] (2) Premixing and wet granulation: Add guanidine hydrochloride 2, microcrystalline cellulose lactose mixture and cross-linked carboxymethyl cellulose sodium into a wet mixing granulator for stirring and premixing, and then add a binder solution under stirring conditions for wet granulation; control the injection speed of the binder solution and spray the binder solution evenly, so that the duration of the binder solution injection process is 170 seconds, and the granulation time after the injection is completed is 160 seconds; (3) Drying and granulation: Dry at 52-54℃, and the drying loss is not higher than 1.2%; the dried granules are added to a granulator, and the sieve aperture of the granulator is 2.0mm;
[0047] (4) Tableting: Add magnesium stearate to the granules and press into tablets to obtain tablet cores.
[0048] (5) Coating: Coating is performed using a spray coating machine until the coating weight gain reaches 5 wt%. The coating is then cured and dried at room temperature for 48 hours to obtain morpholino hydrochloride tablets.
[0049] 3. Test results: The dissolution curve of the prepared morpholino hydrochloride tablets in water was measured, and the results are shown in the following table.
[0050]
[0051] The morpholinoguanidine hydrochloride tablets prepared in Examples 1-6 not only have similar dissolution between different examples, with a dissolution rate of not less than 85% within 30 min, but also have stable dissolution between the same batches (the RSD of the dissolution result at the first time point of 3 min is less than 10%; the RSD of the dissolution result from 6 min to 30 min is less than 5%).
[0052] Comparative Examples 1-3: Effect of Morphoguanidine hydrochloride particle size 1. Prescription composition: The morpholino hydrochloride used is shown in the following table, and the rest is the same as in Example 1.
[0053] 2. Preparation method: Same as Example 1.
[0054] 3. Test results: The dissolution curve of the prepared morpholino hydrochloride tablets in water was measured, and the results are shown in the following table.
[0055]
[0056] Comparative analysis of Example 1 and Comparative Examples 1-3 revealed that the particle size of morpholino hydrochloride affected the dissolution of morpholino hydrochloride tablets. Only morpholino hydrochloride with a specific particle size range (D 90 15-20μm, D 50 The prepared morpholino hydrochloride tablets with a particle size of 8-12 μm have high dissolution (dissolution within 30 min is not less than 85%) and stable dissolution (RSD of the dissolution result at the first time point of 3 min is less than 10%; RSD of the dissolution result from 6 min to 30 min is less than 5%). When morpholino hydrochloride with other particle sizes is used, the prepared morpholino hydrochloride tablets dissolve too slowly (such as comparative example 3) and are unstable (RSD of the dissolution results at the first time point of 3 min and the second time point of 6 min is higher than 10%; RSD of the dissolution results at the third time point of 10 min and the fourth time point of 15 min is higher than 5%).
[0057] Comparative Example 4-5: Effect of Microcrystalline Cellulose Type 1. Formulation: The types of microcrystalline cellulose used are shown in the following table, and the rest are the same as in Example 1.
[0058]
[0059] 2. Preparation method: Same as Example 1.
[0060] 3. Test results: The dissolution curve of the prepared morpholino hydrochloride tablets in water was measured, and the results are shown in the following table.
[0061]
[0062] Comparative analysis of Example 1 and Comparative Examples 4-5 revealed that at the beginning of preparation (0 days), the type of auxiliary material microcrystalline cellulose did not affect the dissolution behavior of the morpholino hydrochloride tablets. Whether it was the microcrystalline cellulose KG802 of Example 1, or KG802 or KG1000 of Comparative Examples 4-5, the prepared morpholino hydrochloride tablets had high dissolution (dissolution within 30 minutes was not less than 85%) and stable dissolution (RSD of the dissolution result at the first time point of 3 minutes was less than 10%; RSD of the dissolution result from 6 minutes to 30 minutes was less than 5%). However, when accelerated for 6 months, as shown in the data of Example 7, the morpholino hydrochloride tablets of Comparative Examples 4-5 had unstable dissolution (RSD of the dissolution result at the first time point of 3 minutes was higher than 10%; RSD of the dissolution result at the second time point of 6 minutes and the third time point of 10 minutes was higher than 5%), and the product quality difference was large. Therefore, KG802 is preferred.
[0063] Comparative Examples 6-7: Effect of Povidone Type 1. Prescription composition: The polyvidone type used is shown in the following table, and the rest is the same as in Example 1.
[0064]
[0065] 2. Preparation method: Same as Example 1.
[0066] 3. Test results The dissolution curve of the prepared morpholino hydrochloride tablets in water was measured, and the results are shown in the following table.
[0067]
[0068] By comparing and analyzing Example 1 and Comparative Example 7, it was found that when using povidone K90 to prepare morpholino hydrochloride tablets, there was a problem of unstable dissolution at the beginning of preparation (0 days) (the RSD of the dissolution result at the first time point of 3 minutes was higher than 10%; the RSD of the dissolution result at the second time point of 6 minutes and the third time point of 10 minutes was higher than 5%), and the quality differences among products prepared in the same batch were large.
[0069] Comparative analysis of Example 1 and Comparative Example 6 revealed that at the beginning of preparation (0 days), the use of povidone K30 did not affect the dissolution behavior of the morpholino hydrochloride tablets, and the prepared morpholino hydrochloride tablets had high solubility (dissolution within 30 min was not less than 85%) and stable dissolution (RSD of the dissolution result at the first time point of 3 min was less than 10%; RSD of the dissolution result from 6 min to 30 min was less than 5%), but when accelerated for 6 months, as shown in the data of Example 7, the morpholino hydrochloride tablets of Comparative Example 6 had unstable dissolution (RSD of the dissolution result at the first time point of 3 min was higher than 10%; RSD of the dissolution result at the second time point of 6 min and the third time point of 10 min was higher than 5%), and the quality differences in the products prepared in the same batch were large. Therefore, povidone K25 is preferred.
[0070] Comparative Examples 8-9: Effect of Microcrystalline Cellulose Lactose Mixture 1. Prescription composition: Same as Example 1.
[0071] 2. Preparation method: Step (1)-① is as shown in the following table, and the remaining steps are the same as in Example 1
[0072] 3. Test results: The dissolution curve of the prepared morpholino hydrochloride tablets in water was measured, and the results are shown in the following table.
[0073]
[0074] Comparative analysis of Example 1 and Comparative Examples 8-9 found that at the beginning of preparation (0 days), the mixing method and particle size of microcrystalline cellulose lactose did not affect the dissolution behavior of morpholino hydrochloride tablets. Whether it was mixed and crushed in Example 1 or crushed and mixed in Comparative Example 8, or different particle sizes were controlled in Comparative Example 9, the prepared morpholino hydrochloride tablets had high dissolution (dissolution within 30 minutes was not less than 85%) and stable dissolution (RSD of the dissolution result at the first time point 3min was less than 10%; RSD of the dissolution result from 6min to 30min was less than 5%), but when accelerated for 6 months, as shown in the data of Example 7, the morpholino hydrochloride tablets of Comparative Examples 8-9 had unstable dissolution (RSD of the dissolution result at the first time point 3min was higher than 10%; RSD of the dissolution result at the second time point 6min and the third time point 10min was higher than 5%), and the product quality difference was large. Therefore, it is preferred to mix and then crush, and the average particle size of the mixture is controlled to be 30-40μm.
[0075] Comparative Examples 10-11: Effect of Coating 1. Prescription composition: The tablet core is the same as in Example 1, and the coating composition is as follows:
[0076] 2. Preparation method: Same as Example 1 3. Test results: The dissolution curve of the prepared morpholino hydrochloride tablets in water was measured, and the results are shown in the following table.
[0077]
[0078] By comparing and analyzing Example 1 and Comparative Example 10, it was found that the composition of the coating solution affects the dissolution behavior. When the weight ratio of ethyl cellulose to maltose in the coating solution was 2:1, the morpholinoguanidine hydrochloride tablet core had unstable dissolution at the beginning of preparation (0 days) (the RSD of the dissolution results at the first time point of 3 min and the second time point of 6 min was higher than 10%; the RSD of the dissolution results at the third time point of 10 min and the fourth time point of 15 min was higher than 5%). The quality differences among products prepared in the same batch were large.
[0079] By comparing and analyzing Example 1 and Comparative Example 11, it was found that at the beginning of preparation (0 day), when the weight ratio of ethyl cellulose to maltose in the coating solution was 1:2, it did not affect the dissolution behavior of the morpholino hydrochloride tablets, and the prepared morpholino hydrochloride tablets had high solubility (not less than 85% dissolution within 30 min) and stable dissolution (RSD of the dissolution result at the first time point of 3 min was less than 10%; RSD of the dissolution result from 6 min to 30 min was less than 5%). However, Test Example 1 showed that the morpholino hydrochloride tablets prepared in Comparative Example 11 released morpholino hydrochloride in the simulated oral fluid, and released a bitter taste of the drug in actual use, resulting in a poor medication experience.
[0080] Therefore, the preferred ratio of ethyl cellulose to maltose in the coating is 1:1.
[0081] Test Example 1: The guanidine hydrochloride tablets obtained by the preparation methods of Examples 1-6, Comparative Examples 4-6, Comparative Examples 8-9, and Comparative Example 11 were used as samples, and 3 tablets were randomly taken from each group. 10 mL of artificial saliva was taken out in a small cup, and a guanidine hydrochloride tablet was added. At 30s and 60s, part of the solution was taken out for content detection, and the dissolution amount (%) of guanidine hydrochloride at 30s and 60s was calculated. The average value of the test data is summarized as shown in the following table.
[0082]
[0083] The guanidine hydrochloride tablets prepared in Examples 1-6, Comparative Examples 4-6, and Comparative Examples 8-9 are sustained-released in simulated oral fluid, and do not release the bitter taste of the drug within 60 seconds in actual medication, thereby improving the medication experience; the guanidine hydrochloride tablets prepared in Comparative Example 11 release guanidine hydrochloride in simulated oral fluid, and release the bitter taste of the drug within 60 seconds in actual medication, thereby poor the medication experience.
[0084] Example 7: Stability Test The morpholinoguanidine hydrochloride tablets prepared in Examples 1-6, Comparative Examples 4-6, and Comparative Examples 8-9 were placed at a temperature of 40°C ± 2°C and a relative humidity of 75% ± 5% (accelerated) for 6 months. Samples were taken at the end of the 6th month and the dissolution curves were measured in water. The results are shown in the following table.
[0085] Example 1-6 Dissolution curve of morpholinoguanidine hydrochloride tablets in water after 6 months of acceleration
[0086] Dissolution curves of morpholinoguanidine hydrochloride tablets in water after accelerated 6 months in comparative examples 4-6 and 8-9
[0087] The dissolution behavior of the morpholinoguanidine hydrochloride tablets prepared in Examples 1-6 of the present invention was not significantly changed after being placed under accelerated conditions for 6 months, indicating that the dissolution of the morpholinoguanidine hydrochloride tablets prepared in the present invention was stable.
[0088] The tablet compositions of morpholino hydrochloride prepared in Comparative Examples 4-6 and Comparative Examples 8-9 were unstable in dissolution after accelerated storage for 6 months.
Claims
1. A morpholino hydrochloride tablet, comprising a core and a coating, wherein the core is made of the following raw materials in percentage by weight: 32%-45% morpholino hydrochloride, 20%-25% microcrystalline cellulose, 25%-30% lactose, 3%-8% cross-linked carboxymethyl cellulose sodium, and povidone K 25 3%-5%, magnesium stearate 1.2%-2%; The particle size D of the morpholino hydrochloride 90 15-20μm, D 50 8-12μm; The microcrystalline cellulose is preferably microcrystalline cellulose KG802.
2. The morpholinoguanidine hydrochloride tablets according to claim 1, characterized in that: The tablet core is made of the following raw materials in percentage by weight: 35%-40% morpholino hydrochloride, 21%-24% microcrystalline cellulose, 25%-30% lactose, 3%-8% cross-linked carboxymethyl cellulose sodium, and povidone K. 25 3%-5%, magnesium stearate 1.2%-2%.
3. The morpholinoguanidine hydrochloride tablets according to claim 1, characterized in that: The tablet core is made of the following raw materials in percentage by weight: 36%-39% morpholino hydrochloride, 20%-25% microcrystalline cellulose, 25%-30% lactose, 3%-8% cross-linked carboxymethyl cellulose sodium, and povidone K. 25 3%-5%, magnesium stearate 1.2%-2%.
4. The morpholinoguanidine hydrochloride tablets according to claim 1, characterized in that: The tablet core is made of the following raw materials in percentage by weight: 36%-39% morpholino hydrochloride, 21%-24% microcrystalline cellulose, 25%-30% lactose, 3%-8% cross-linked carboxymethyl cellulose sodium, and povidone K. 25 3%-5%, magnesium stearate 1.2%-2%.
5. The morpholinoguanidine hydrochloride tablets according to claim 1, characterized in that: The coating is made of the following raw materials in percentage by weight: 35%-50% ethyl cellulose, 35%-50% maltose, 1.2%-2.0% talcum powder, 2%-3% titanium dioxide, and povidone K. 25 5%-10%.
6. The morpholinoguanidine hydrochloride tablets according to claim 5, characterized in that: The coating is made of the following raw materials in percentage by weight: 32%-37% ethyl cellulose, 32%-37% maltose, 1.2%-2.0% talcum powder, 2%-3% titanium dioxide, and povidone K. 25 5%-10%.
7. A method for preparing the morphine guanidine hydrochloride tablets according to any one of claims 1 to 6, characterized in that: The steps include: Pretreatment of auxiliary materials; ① Mix microcrystalline cellulose and lactose, grind them into a mixture with an average particle size of 30-40 μm, and obtain a microcrystalline cellulose lactose mixture for later use; ②Polyvidone K25 is dissolved in water to prepare a solution with a concentration of 5wt%-10wt% as an adhesive solution for standby use; ③ Ethyl cellulose, maltose, talcum powder, titanium dioxide, povidone K 25 Add ethanol 20-25 times the weight of the coating, stir, and homogenize to obtain a coating solution for later use; (2) Premixing and wet granulation: Adding guanidine hydrochloride, microcrystalline cellulose lactose mixture and cross-linked carboxymethyl cellulose sodium into a wet mixing granulator for stirring and premixing, and then adding a binder solution under stirring conditions, wet granulating; controlling the injection speed of the binder solution, spraying the binder solution evenly, making the duration of the binder solution injection process 140-180 seconds, and the granulation time after the injection is completed is 120-180 seconds; (3) Drying and granulation: Dry at 50-55℃, and the drying loss is not higher than 1.2%; the dried granules are added to a granulator, and the sieve aperture of the granulator is 2.0mm; (4) Tableting: adding magnesium stearate to the granules and tableting to obtain tablet cores; (5) Coating: The coating is performed by a spray coating machine until the coating weight gain reaches 5 wt%-7 wt%. The coating is then cured and dried at room temperature to obtain morpholinoguanidine hydrochloride tablets.
8. The preparation method according to claim 7, characterized in that: In step (3), the temperature is preferably 52-54°C, and more preferably dried under reduced pressure and vacuum.
9. The preparation method according to claim 7, characterized in that: In the step (3), the particles are granulated, and the particle size distribution of the particles after granulation is: 。
Citation Information
Patent Citations
Preparation method and product of Ganmaoqing tablet
CN116942743A
Taste-masked oral formulations of influenza antivirals
US20120093738A1